PENUMBUHAN KEWIRAUSAHAAN MASYARAKAT DI KABUPATEN PONOROGO - Bambang Kusbandrijo (Faculty of Social and Political Science, 2014)
Growth and development in a country Is economy can not be separated from the role of private entrepreneurs large, medium and .small Not possible growth and development of road infrastructure and buildings, as well as goods - and services required by humans in the absence of the role of entrepreneurs. Government policies to foster entrepreneurial venture among rural communities is the real answer to solve the problem of poverty as well as a form of empowerment. Describe and analyze the perceptions and attitudes towards entrepreneurship growth. Finding models of economic growth of rural communities based on local wisdom . The method used is descriptive qualitative. The research findings; that the people are interested to become entrepreneurs, but they expressed less agree if the business that occupied a new business . They would agree that business will be done is to develop existing business . About the obstacles to he faced when they went into business they stated many obstacles, but the government support program growth entrepreneurs. Empowerment and entrepreneurial growth is memberikani government intervention in the economy and politics via affirmative action , NGOs, PT, figures, as private actors to improve human resources and organizers. Poor community empowerment